Congenital hyperinsulinism and surgical outcome in a single tertiary center in Brazil - Raphael Del Roio Liberatore, Junior; Isabella Christina Mazzaro Monteiro; Flavio de Oliveira Pileggi; Wellen Cristina Canesin; Lourenço Sbragia (Elsevier, 2024)
Objective: Congenital hyperinsulinism (CHI) is a heterogeneous genetic disease characterized by increased insulin secretion and causes persistent hypoglycemia in neonates and infants due to dysregulation of insulin secretion by pancreatic β cells. Babies with severe hypoglycemia and for whom medical treatment has been ineffective usually require surgical treatment with near-total pancreatectomy. To evaluate the clinical and surgical aspects affecting survival outcomes in babies diagnosed with CHI in a single tertiary care center. Methods: Retrospective Cohort study involving a single university tertiary center for the treatment of CHI. The authors study the demographics, clinical, laboratory, and surgical outcomes of this casuistic. Results: 61 % were female, 39 % male, Birth weight: 3576 g (±313); Age of onset of symptoms: from the 2nd hour of life to 28 days; Time between diagnosis and surgery ranged between 10 and 60 days; Medical clinical treatment, all patients received glucose solution with a continuous glucose infusion and diazoxide. 81 % of the patients used corticosteroids, 77 %. thiazide, 72 % octreotide, 27 % nifedipine; Neurological sequelae during development and growth: 54 % had some degree of delay in neuropsychomotor development, 27 % obesity. Surgery was performed open in 6 and 12 minimally invasive surgery (MIS). Histopathology: 2 focal and 16 diffuse, Length of stay (days) was lower in MIS (p < 0.05). Survival was 100 %. Conclusions: CHI is a rare and difficult-to-manage tumor that must be performed in a multidisciplinary and tertiary center. Most surgical results are good and the laparoscopic approach to disease has been the best choice for patients.